The Effect of Firmware Settings on Engraving Results of a CNC Laser Engraver Machine - Anrinal, Anrinal; Zamhari, Muhammad Apri; Yanto, Asmara (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2024)
This study aims to determine the effect of setting the firmware on the time and results of the engraving and to analyze the impact of the engraver variable on the CNC Laser Engraving machine. The test results of the cnc laser engraving firmware setting were obtained from several stages of testing the predetermined settings such as the Axis maximum rate and Axis acceleration settings, in order to find the appropriate Axis maximum rate and Axis acceleration settings for the laser engraving process. Tests with the Axis maximum rate setting are carried out with variables 600 mm/min,1200 mm/min,1800 mm/min aiming to find the ideal speed, Tests with Axis acceleration settings are carried out with variables 20 mm/s2, 40 mm/s2, 60mm/s2. aims to find the ideal acceleration by looking at the stability of the results and comparing the test data. axis maximum rate (110 and 111) 600 mm/min and axis acceleration (120 and 121) 40 mm/s2, taking into account the engraving time and the resulting clean, non-blur engraving results and the resulting engraving line width. Based on the study, it is recommended for users to be careful in setting the firmware for maximum and clean results. Based on the speed and acceleration test data on the engraving scale, the faster the engraving process, the smaller and blurry the resulting scale (width of the engraving) will be.